Pengaruh Metode Latihan Mini Game Terhadap Kemampuan Passing Bawah Atlet Bolavoli di Mvc Bengkulu Tengah - Munawaroh Munawaroh; Ajis Sumantri; Martiani Martiani (Educative Sportive, 2026)
Freestyle swimming is the fastest style, relying heavily on arm stroke power and leg kick propulsion. To improve speed, coaches often utilize auxiliary equipment, one of which is swim fins. This study aims to determine the effect of fins training on improving 50-meter freestyle swimming speed among athletes at Star Gloz Swimming Club. This study employed a quantitative method with a pre-experimental one-group pretest-posttest design. The population consisted of Star Gloz Swimming Club athletes, with a sample of 10 athletes selected through purposive sampling. The research instrument was a 50-meter freestyle speed test using a stopwatch. The athletes received fins training treatment for 8 sessions. Data analysis included prerequisite tests (normality and homogeneity) and hypothesis testing using a paired sample t-test with SPSS assistance. The results showed the average pretest time was 39.59 seconds, while the posttest average improved to 36.69 seconds. The t-test result showed a t-count value of 15.682, which is greater than the t-table (2.262), with a significance value of 0.000 < 0.05. This indicates that H0 is rejected and Ha is accepted. It is concluded that there is a significant effect of fins training on improving 50-meter freestyle swimming speed among athletes at Star Gloz Swimming Club. Fins training is effective in increasing leg muscle strength and ankle flexibility, contributing to increased propulsion and swimming speed.